Areopagitica : a Speech for the Liberty of Unlicensed Printing to the Parliament of England. - Milton, John (Floating Press, 1753)
Areopagitica: A speech for the Liberty of Unlicensed Printing to the Parliament of England is John Milton's famous tract against censorship. Published in 1644, Areopagitica is named after a speech by Isocrates, a fifth century BC Athenian orator. The work is counted as one of the most influential and inspired defenses of the right to freedom of expression in history. It is also a personal issue for Milton who was submitted to censorship himself when he tried to publish ...